Are covered bonds a substitute for mortgage-backed securities? - Santiago Carbó-Valverde; Richard J. Rosen; Francisco Rodríguez-Fernández (Federal Reserve Bank of Chicago, 2011)
Covered bonds and mortgage-backed securities both allow mortgages to be financed with duration-matched bonds. Given the problems in the MBS market during the financial crisis, some suggest that covered bonds might be a substitute for MBS. We examine the use of covered bonds and MBS in the U.S. and Europe, finding that the two are used for different purposes. Covered bonds are used more to increase liquidity than are MBS. MBS are more often used in ways consistent with exploiting some kinds of agency problems.
Keywords: 330